Osteopathic manual therapy in heart failure patients: A randomized clinical trial. Issue 2 (April 2018) - Thomaz, Sergio R.; Teixeira, Felipe A.; de Lima, Alexandra C.G.B.; Cipriano Júnior, Gerson; Formiga, Magno F.; Cahalin, Lawrence Patrick
Abstract: Background: Heart Failure (HF) patients usually present with increased arterial resistance and reduced blood pressure (BP) leading to an impaired functional capacity. Osteopathic Manual Therapy (OMT) focused on myofascial release techniques (MRT) and in the balancing of diaphragmatic tensions, has been shown to improve blood flow in individuals using the resistive index (RI). However, its effects in HF patients have not been examined. Purpose: To evaluate the acute response of selected osteopathic techniques on RI, heart rate (HR), and BP in patients with HF. Methods: Randomized-controlled clinical trial of HF patients assigned to MRT (six different techniques with three aimed at the pelvis, two at the thorax, and one at the neck for 15 min) or Control group (subjects in supine position for 15 min without intervention). The RI of the femoral, brachial and carotid arteries was measured via doppler ultrasound while HR and BP were measured via sphygmomanometry before and after a single MRT or control intervention. Results: Twenty-two HF patients equally distributed (50% male, mean age 53 years; range 32–69 years) (ejection fraction = 35.6%, VO2peak : 12.9 mL/kg −1 min −1 ) were evaluated. We found no intra or inter group differences in RI of the carotid (ΔMRT : 0.07% vs ΔControl :11.8%), brachial (ΔMRT :0.17% vs ΔControl : 2.9%), or femoral arteries (ΔMRT :1.65% vs ΔControl : 0.97%) (P > 0.05) and no difference in HR or BP (ΔMRT :0.6% vs ΔControl : 3%), (P > 0.05). Conclusion: A single MRT session did not significantly change the RI, HR, or BP of HF patients.